GSTZ1‐1 Deficiency Activates NRF2/IGF1R Axis in HCC via Accumulation of Oncometabolite Succinylacetone. (28th June 2019) - Yang, Fan; Li, Jingjing; Deng, Haijun; Wang, Yihao; Lei, Chong; Wang, Qiujie; Xiang, Jin; Liang, Li; Xia, Jie; Pan, Xuanming; Li, Xiaosong; Long, Quanxin; et al.
Abstract: The IGF1R signaling is important in the malignant progression of cancer. However, overexpression of IGF1R has not been properly assessed in HCC. Here, we revealed that GSTZ1‐1, the enzyme in phenylalanine/tyrosine catabolism, is downregulated in HCC, and its expression was negatively correlated with IGF1R. Mechanistically, GSTZ1‐1 deficiency led to succinylacetone accumulation, alkylation modification of KEAP1, and NRF2 activation, thus promoting IGF1R transcription by recruiting SP1 to its promoter. Moreover, inhibition of IGF1R or NRF2 significantly inhibited tumor‐promoting effects of GSTZ1 knockout in vivo . These findings establish succinylacetone as an oncometabolite, and GSTZ1‐1 as an important tumor suppressor by inhibiting NRF2/IGF1R axis in HCC. Targeting NRF2 or IGF1R may be a promising treatment approach for this subset HCC. Synopsis: The phenylalanine/tyrosine catabolism enzyme glutathione S‐transferase zeta 1 (GSTZ1‐1) is downregulated in hepatocellular carcinoma (HCC), but its mechanistic involvement remains unclear. Here, GSTZ1‐1 is shown to suppress tumor growth via controlling levels of the metabolite succinylacetone, and dependent KEAP1/NRF2/IGF‐1R signaling. GSTZ1‐1 expression is decreased in HCC and correlates with poor prognosis. GSTZ1‐1 suppresses hepatoma cell proliferation in vitro and in vivo . Depletion of GSTZ1‐1 results in accumulation of succinylacetone. Increased succinylacetone stabilizes NRF2 by alkylating cysteine residues of KEAP1. Gstz1 −/− mice show increased HCC, rescued by targeting the NRF2‐IGF1R anti‐apoptotic pathway. Abstract : The detoxification enzyme GSTZ1‐1 acts as tumor suppressor in liver cancer controlling anti‐apoptotic IGF1R signalling.